Transport Planning Model for India Project Leader : Dr. M. Q. Dalvi Volume I - Planning Commission (Planning Commission, 1982)
Transport has been at the focus of attention in India’s developmental effort since the inception of planning era in the country in 1951. In every Five Year Plan, transport sector has accounted for a sizeable chunk of the country's gross national investment. The share of transport in total plan outlays has ranged from 22 per cent in the First Plan and 24 per cent in the Second Plan to 12 per cent in the Sixth Plan.
Planning Commission
Planning Commission